1997
DOI: 10.1210/jcem.82.9.4206
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Plasma Cortisol Levels in Extremely Low Birth Weight Infants1

Abstract: Cortisol is secreted by children and adults in a pulsatile pattern of 15-30 peaks and nadirs each day with a circadian rhythm. Newborns are known to lack the circadian pattern, leading to uncertainty about the appropriate time for blood sampling for assessment of adrenal function. Because extremely low birth weight (ELBW) infants may manifest signs of adrenal insufficiency, knowledge of the pattern of cortisol levels is necessary to guide the appropriate timing of blood sampling. To define the pattern of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As summarized in Table 4, due to the difficulties in sample collection and analysis, studies on hormonal rhythms in preterm infants are still very limited until now, and nearly all focused on the cortisol and melatonin rhythms. With regard to the cortisol, due to the immature of HPA axis (Bolt et al, 2002), no significant circadian or ultradian rhythms were observed during the early postnatal periods (Economou et al, 1993;Jett et al, 1997;Kidd et al, 2005;Dorn et al, 2014). Nevertheless, studies have found that healthy preterm infants had higher nighttime cortisol levels than daytime at birth, and that cortisol levels tended to decrease gradually after birth (Kidd et al, 2005;Dorn et al, 2014).…”
Section: Hormonal Rhythmsmentioning
confidence: 99%
“…As summarized in Table 4, due to the difficulties in sample collection and analysis, studies on hormonal rhythms in preterm infants are still very limited until now, and nearly all focused on the cortisol and melatonin rhythms. With regard to the cortisol, due to the immature of HPA axis (Bolt et al, 2002), no significant circadian or ultradian rhythms were observed during the early postnatal periods (Economou et al, 1993;Jett et al, 1997;Kidd et al, 2005;Dorn et al, 2014). Nevertheless, studies have found that healthy preterm infants had higher nighttime cortisol levels than daytime at birth, and that cortisol levels tended to decrease gradually after birth (Kidd et al, 2005;Dorn et al, 2014).…”
Section: Hormonal Rhythmsmentioning
confidence: 99%
“…Neonates do not develop this circadian rhythm until 2-3 months after birth 7,8 . In addition, neonates in the intensive care setting may not establish their circadian rhythm until much later.…”
Section: Introductionmentioning
confidence: 99%